2015
DOI: 10.1038/srep16884
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of human induced pluripotent stem cell-derived hepatocytes in immunocompetent mice via 3D co-aggregation and encapsulation

Abstract: Cellular therapies for liver diseases and in vitro models for drug testing both require functional human hepatocytes (Hum-H), which have unfortunately been limited due to the paucity of donor liver tissues. Human pluripotent stem cells (hPSCs) represent a promising and potentially unlimited cell source to derive Hum-H. However, the hepatic functions of these hPSC-derived cells to date are not fully comparable to adult Hum-H and are more similar to fetal ones. In addition, it has been challenging to obtain func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 60 publications
(147 reference statements)
3
72
0
Order By: Relevance
“…This promoted an evident hepatic differentiation of iPSCs when compared to single‐cell culture conditions. In addition, human cocultured encapsulated cells were transplanted in immunocompetent mice without causing immune rejection for at least 24 days 21. However, the actual applicability of the encapsulated coculture system approach needs to be further explored in specific disease models where additional parallel strategies aimed at reducing potential foreign body fibrotic reactions22, 23 and improving neovascularization24, 25 should be considered.…”
Section: Implantable Technologies For Liver Therapiesmentioning
confidence: 99%
“…This promoted an evident hepatic differentiation of iPSCs when compared to single‐cell culture conditions. In addition, human cocultured encapsulated cells were transplanted in immunocompetent mice without causing immune rejection for at least 24 days 21. However, the actual applicability of the encapsulated coculture system approach needs to be further explored in specific disease models where additional parallel strategies aimed at reducing potential foreign body fibrotic reactions22, 23 and improving neovascularization24, 25 should be considered.…”
Section: Implantable Technologies For Liver Therapiesmentioning
confidence: 99%
“…These data are used to generate a replacement scaffold for organ construction using either a 3-D printer [29] or an individually-modified decellularized organ scaffold. Either ex vivo tissue engineering with nanotechnology [30] or in vivo directed pleuripotent stem cell transplantation are used to recreate the organ in its entirety [31,32].…”
Section: Fig 1 Computer Driven Intensive Carementioning
confidence: 99%
“…Immunodeficient chimeric mice with human hepatocytes have been widely used in pharmaceutical ADMET research (Kakuni et al, 2012;Schulz-Utermoehl et al, 2012). The transplantation study of hiPSC-derived hepatocytes to immunodeficient mice has been reported very recently, but their drug metabolizing activities remained to be determined (Song et al, 2015).…”
Section: Discussionmentioning
confidence: 99%